2013
DOI: 10.5578/tt.6252
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of GST polymorphism in relation to age in COPD and lung cancer

Abstract: ÖZET KOAH ve akciğer kanserinde yaşla ilişkili olarak GST polimorfizmi karşılaştırmalı çalışma (OR= 1.87; 95%; p= 0.002). GSTM1 null akciğer kanseriyle ilişkili bulunmadı. Alt grup analizinde GSTM1 null polimorfizmi [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] OR= 3.20; 95%; p= 0.001), akciğer kanserli hastalar ile kontrol arasında aynı yaş grubunda fark yoktu (55.6%/44.4% OR= 1.07; p= 0.774

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Figure shows the selection and inclusion process. Thirty‐seven included articles were conducted in 16 countries: Korea, Japan, China, Brazil, Russia, United States, Turkey, Slovakia, Egypt, Tunisia, India, Croatia, Bulgaria, Kazakhstan, New Zealand and Serbia . Twenty‐three articles from 5 countries (Korea, Japan, China, India and Kazakhstan) were performed in Asian populations, 11 from 9 countries (Brazil, Russia, United States, Turkey, Bulgaria, Slovakia, New Zealand, Croatia and Serbia) in Caucasian populations and 3 from 2 countries (Egypt and Tunisia) in African populations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure shows the selection and inclusion process. Thirty‐seven included articles were conducted in 16 countries: Korea, Japan, China, Brazil, Russia, United States, Turkey, Slovakia, Egypt, Tunisia, India, Croatia, Bulgaria, Kazakhstan, New Zealand and Serbia . Twenty‐three articles from 5 countries (Korea, Japan, China, India and Kazakhstan) were performed in Asian populations, 11 from 9 countries (Brazil, Russia, United States, Turkey, Bulgaria, Slovakia, New Zealand, Croatia and Serbia) in Caucasian populations and 3 from 2 countries (Egypt and Tunisia) in African populations.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 shows the selection and inclusion process. Thirty-seven included articles were conducted in 16 countries: Korea, 19,20 Japan, 21,22 China, [23][24][25][26][27][28][29][30][31][32] Brazil, 33 Russia, 34,35 United States, 36 Turkey, 37 Slovakia, 38 Egypt, 39,40 Tunisia, 41 India, [42][43][44][45][46][47][48][49] Croatia, 50 Bulgaria, 51 Kazakhstan, 52 New Zealand 53 and Serbia. 54,55 Twenty-three articles from 5 countries The main characteristics of included studies were present in Table 1.…”
Section: Characteristics Of Eligible Case-control Studiesmentioning
confidence: 99%
“…Several genome-wide association studies (GWAS) have so far identified 16 susceptibility loci (P 5.00 3 10 -8 ) worldwide that are associated with lung cancer risk [Wang et al, 2008;Hu et al, 2011;Dong et al, 2012] and four loci out of them showed evidences of association of lung cancer risk in smokers [Dong et al, 2012]. However, most of these reports were based on Caucasian and Chinese populations, and many identified risk alleles have not been adequately evaluated in Indian population in spite of several case-control investigations on the Indian population from different geographical zones [Sobti et al, 2003[Sobti et al, , 2004[Sobti et al, , 2008[Sobti et al, , 2009Sreeja et al, 2005Sreeja et al, , 2008aSreeja et al, , 2008bSreeja et al, , 2008cJain et al, 2005;Pachouri et al, 2006Pachouri et al, , 2007Kotnis et al, 2008;Shah et al, 2008;Singh et al, 2010Singh et al, , 2016Tilak et al, 2011Tilak et al, , 2013Ihsan et al, 2011a,;Kant Shukla et al, 2013;Natukula et al, 2013;Shukla et al, 2013;Bag et al, 2014;Phukan et al, 2014;Saikia et al, 2014;Uppal et al, 2014;Sharma et al, 2015;Kumari et al, 2016;Peddireddy et al, 2016]. To date, researchers have not been able to delineate the overall effect of the genes and the genetic variations on lung cancer susceptibility in the populations of Indian origin, due to certain conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…That is why the GST gene variants associated with a decline or lack of catalytic activity might increase the risk of T2D [17]. Moreover, it is known that GST gene polymorphisms are involved in the development of malignancies, such as gastric cancer [18], lung cancer [19] or colorectal cancer [7].…”
Section: Discussionmentioning
confidence: 99%